The Science of Small Arms Ballistics. - Buckmore, Jr., Alvah (Apple Academic Press, 2018)
"This very unique and very different book is a comprehensive study of the science of small arm ballistics--from interior and exterior ballistics to terminal ballistics. The science of small arms ballistics is seriously underdeveloped and underappreciated. The volume provides a complete grasp of the entire subject. It fills a legitimate need for a book that covers the entire science of small arm ballistics. The Science of Small Arms Ballistics serves as a manual for both members of academia and members of the recreational shooting community throughout the world. Though it contains extensive mathematical formulas (58 of them), the book demonstrates the relationships between the physical variables and their real-world engineering applications. The author defines the science of ballistics by breaking it down into its major and logical categories and then explaining the basic patterns and relationships in a way the reader can understand and use toward the solution of problems, either to design ammunition for a particular gun or a gun for any particular ammunition. Through extensive research, the author has worked out relationships in the science of small arms ballistics mathematically and puts forth and explains new theories on small arms ballistics, such the field-effect and the field-effect over trajectory and time, along with new theories in interior, exterior, and terminal ballistics. This includes a scientific study of time, evolving from the study of the field-effect theory in exterior ballistics. Each equation, which describes a mathematical relationship, such as transfer of energy, will have an engineering application for the shooter with a design problem. Some equations, such as the calculation of bullet length with a given muzzle velocity and rate of twist, represent manipulations of those equations, such as the rate of twist and bullet spin. Some other equations represent a set of mathematical instructions to resolve a technical problem, such as the computation of trajectory or depth of penetration of living tissue in real-time. An exhaustive example is included to help the reader in the proper way to reload ammunition for a particular gun and its rate of twist, along with the formulas to calculate the ballistic parameters for this purpose, including several computer programs to calculate and predict these parameters. This revolutionary work, written by an acknowledged pioneer in the field, will be a rich resource for anyone interested in the engineering and theory of small arms ballistics."--Provided by publisher.
27: Reflection of Kinetic Energy28: Acceptance of Kinetic Energy; 29: Theory of Penetration; 30: Calculating the Expectant Depth of Penetration into Animal Issue; 31: Ballistic Reflection Coefficient; 32: Ballistic Reflection Power; 33: Ballistic Penetrating Power; 34: Ballistic Work Function; Bibliography; Index
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING / Mechanical; Ballistics; Firearms